Pengaruh Sitokinin Eksogen dan Sukrosa terhadap Produksi Biomassa dan Alkaloid Canthinone di dalam Kultur Suspensi Sel Pasak Bumi (Eurycoma longifolia Jack.) - Mahmud Siregar, Luthfi Aziz (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2010)
The effect of addition cytokinins and modification of sucrose concentration on growth and alkaloid canthinoneproduction in cell suspension cultures of Eurycoma longifilia Jack were studied. The additions of cytokines, BAand kinetin, show effect on the production of biomass and alkaloid in cell suspension of E. longifilia Jack. Theoptimum totals of two-alkaloids were obtained on addition 4.44 μM BAP and without kinetin, respectively. Theaddition of 4.44 μM BA (6-benzyladenine) into TAM medium stimulated increased total of 9-hydroxycanthine-6-one,but decreased total of 9-methoxycanthin-6-one. While the addition of 2.32 - 9.29 μM kinetin (6-furfurylaminopurine)into TAM medium decreased total of two alkaloids (from 0.582 mg to 0.461 - 0.257 mg per 25 ml medium). Whensucrose concentration in TAM medium was increased from 3% to 5%, production of biomass would increase from0.374 g to 0.585 g dry weight per 25 ml medium. While total of two-alkaloids increase from 0.328 mg to 0.441 mgper 25 ml medium when concentration of sucrose in TAM medium was increased from 3% to 4% sucrose.